(untitled) (Journal of Geography and Environmental Management, 2018)
As socio-economic phenomenon of tourism has a significant impact on the development of the territory, reflecting the degree of cooperation with enterprises of socio-cultural sphere, the transport sector, hotel and spa complex. The development of competitive advantages of tourism in order to increase the efficiency of the regional economy as a whole provides an improvement of the quality of life. The article examines the state and prospects of development of tourist industry in the Belgorod region. Article is made in the framework of grant of the Russian Federation President’s for state support of young Russian scientists – candidates of sciences (theme “Development of competitive advantages of the tourism sphere with aim to improve the efficiency of the regional economy”, MK-8062.2016.6).